2014
DOI: 10.1024/1010-0652/a000122
|View full text |Cite
|
Sign up to set email alerts
|

Variieren die Selbstkonzeptdifferenzen in Abhängigkeit vom Leistungsniveau? Differenzielle Zusammenhänge in Deutsch, Englisch und Mathematik

Abstract: Möller und Pohlmann (2010) konnten größere Differenzen der mittleren Ausprägungen der Fähigkeitsselbstkonzepte zwischen über- und durchschnittlich leistungsstarken Schülerinnen und Schülern als zwischen unter- und durchschnittlich leistungsstarken Schülerinnen und Schülern für das Fach Deutsch nachweisen. Unter Verwendung derselben Analysemethode soll dieser Befund repliziert und auf die Fächer Englisch und Mathematik erweitert werden. Hierzu werden verschiedene Leistungsmaße (Kompetenzen vs. Noten) und Refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Being surrounded by high achieving students allows for more opportunities for upward comparisons, which relates to a lower academic self-concept; in contrast, belonging to a low achieving group of students, the opportunities for downward comparisons increase, resulting in a more positive academic self-concept (Köller et al 2006). The study by Schurtz et al (2014) found that students with above-average grades reported higher mathematics self-concepts compared with the average performance of their peers (downward comparison), whereas students with below-average grades reported lower mathematics selfconcepts compared to students with class-average grades (upward comparison). Thus, the most salient reference group is usually students' class environment (Wouters et al 2013) and the academic self-concept is impacted by the composition of the class (Dumont et al 2017;Stäbler et al 2017).…”
Section: Mechanisms For the Formation Of Mathematics Self-conceptmentioning
confidence: 98%
“…Being surrounded by high achieving students allows for more opportunities for upward comparisons, which relates to a lower academic self-concept; in contrast, belonging to a low achieving group of students, the opportunities for downward comparisons increase, resulting in a more positive academic self-concept (Köller et al 2006). The study by Schurtz et al (2014) found that students with above-average grades reported higher mathematics self-concepts compared with the average performance of their peers (downward comparison), whereas students with below-average grades reported lower mathematics selfconcepts compared to students with class-average grades (upward comparison). Thus, the most salient reference group is usually students' class environment (Wouters et al 2013) and the academic self-concept is impacted by the composition of the class (Dumont et al 2017;Stäbler et al 2017).…”
Section: Mechanisms For the Formation Of Mathematics Self-conceptmentioning
confidence: 98%
“…Their results provided initial evidence that the strength of the relation between achievement and self-concept varies with students’ level of achievement with stronger relations for higher achieving students and weaker relations for lower achieving students in German (native language education; Möller & Pohlmann, 2010; Schurtz et al, 2014). However, the findings were heterogeneous for English as a foreign language and for mathematics (Schurtz et al, 2014).…”
Section: From Tools To Theories: Linear and Nonlinear Relations Betwe...mentioning
confidence: 99%
“…These studies can be grouped by the analytic strategy they applied. The first group of studies examined mean-level differences in self-concepts in relation to achievement differences by splitting the achievement continuum into discrete groups (i.e., low-, average-, and high-achieving students) using planned contrasts, ANOVAs, or multigroup comparisons in structural equation models (Möller & Pohlmann, 2010;Prast, Van de Weijer-Bergsma, Mioc ˇevic ´, Kroesbergen, & Van Luit, 2018;Schurtz, Pfost, & Artelt, 2014;Van der Beek, Van der Ven, Kroesbergen, & Leseman, 2017). The second group of studies investigated the relation between achievement and self-concept by using polynomial regression analyses (Marsh, 2004;Marsh & Rowe, 1996).…”
Section: From Tools To Theories: Linear and Nonlinear Relations Betwe...mentioning
confidence: 99%
See 2 more Smart Citations